Planning Dhaka as a Global City: A Critical Discourse (Journal of Bangladesh Institute of Planners, 2012)
Cities and city regions are practically observed to be the engines of economic growth in the age of globalization. Cities and their regions thus diversely play important roles in national and international contexts. City provides opportunities for economic growth and development and quality life for its population and services to its outside areas, sometimes exceeding the national boundaries. Globalization has, however, created both opportunities and threats for the survival of cities. To become an active partner in the process of globalization, cities with their regional economic strengths require preparing them with their potentials and removing weaknesses. As a capital city, Dhaka has potentials for becoming a global city with its geopolitical location and economic prospects. It has political and administrative advantages in the national context and scope for utilizing the benefits of urban economics, especially agglomerations, concentration of labor and financial institutions, and business services. The physical growth of the city is, however, associated with many-faceted problems which has to be addressed in its planning and development processes in order to bring functional efficiency of a modern city. The city must be developed in a planned manner to benefit from global market and international investment. The research recommends that Dhaka and its city region should overcome the current weaknesses to utilize its full potential to attract businesses and investments in the future. Dhaka’s physical development and economic growth management must be considered together in order to becoming a global city playing dynamic role in the global market in future.DOI: http://dx.doi.org/10.3329/jbip.v2i0.9552Journal of Bangladesh Institute of Planners Vol. 2, December 2009, pp. 1-12